Biomarkers for Diagnosis, Complications and Therapy Effects in Civilization Diseases Management - Komosinska-Vassev, Katarzyna; Olczyk, Pawel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue contributes original research and review articles on the role of new protein, molecular, and genetic markers used for the diagnosis and progression of civilization diseases, as well as biomarkers useful in the monitoring the effects of the implemented treatment.